2019
DOI: 10.1113/jp278168
|View full text |Cite
|
Sign up to set email alerts
|

Functional and pharmacological properties of triheteromeric GluN1/2B/2D NMDA receptors

Abstract: Key points Triheteromeric NMDA receptors contain two GluN1 and two distinct GluN2 subunits and mediate excitatory neurotransmission in the CNS. Triheteromeric GluN1/2B/2D receptors have functional properties intermediate to those of diheteromeric GluN1/2B and GluN1/2D receptors. GluN1/2B/2D receptors are more sensitive to channel blockade by ketamine and memantine compared to GluN1/2B receptors in the presence of physiological Mg2+. GluN2B‐selective antagonists produce robust inhibition of GluN1/2B/2D recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 73 publications
4
38
0
Order By: Relevance
“…In CA1 PyrCs, following a 10 min wash-in, ifenprodil produced a strong 55 ± 21% block of native NMDAR-EPSCs, reducing the average amplitude from 136 ± 78 to 54 ± 30 pA ( N = 13 rats; r = 0.60, −82.4; CI, −137.4, −27.4; p = 0.009, paired Student’s t test; Fig. 5 C ), consistent with the presence of GluN2B receptor subunits ( Gray et al, 2011 ; Yi et al, 2019 ), but a greater block than for triheteromeric receptors alone ( Hansen et al, 2014 ). This ifenprodil block in CA1 PyrCs was stronger in GluN2A-null rats at 83 ± 13% ( N = 8 rats; r = 0.48, −25.2; CI, −48.7, −1.7; p = 0.039, paired Student’s t test), which is consistent with a loss of GluN2A subunit containing triheteromeric receptors ( Hansen et al, 2014 ).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In CA1 PyrCs, following a 10 min wash-in, ifenprodil produced a strong 55 ± 21% block of native NMDAR-EPSCs, reducing the average amplitude from 136 ± 78 to 54 ± 30 pA ( N = 13 rats; r = 0.60, −82.4; CI, −137.4, −27.4; p = 0.009, paired Student’s t test; Fig. 5 C ), consistent with the presence of GluN2B receptor subunits ( Gray et al, 2011 ; Yi et al, 2019 ), but a greater block than for triheteromeric receptors alone ( Hansen et al, 2014 ). This ifenprodil block in CA1 PyrCs was stronger in GluN2A-null rats at 83 ± 13% ( N = 8 rats; r = 0.48, −25.2; CI, −48.7, −1.7; p = 0.039, paired Student’s t test), which is consistent with a loss of GluN2A subunit containing triheteromeric receptors ( Hansen et al, 2014 ).…”
Section: Resultssupporting
confidence: 64%
“…Pharmacology for the specific NMDAR subunits was as follows: GluN2B-ifenprodil tartrate (10 μ m ) or NAB-14 (10 μ m ), and both were bath applied. As NAB-14 is highly lipophilic ( Yi et al, 2019 ), all tubing was rinsed with 100% ethanol and liberal amounts of distilled water between recordings to ensure full removal of the drug from the surfaces of perfusion tubes. All EPSC amplitudes were recorded at the peak of the EPSC, as measured over a 2 ms peak average.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast to our findings that neither the block of GluN2B nor of GluN2A could alter interneuronal dendritic complexity. Opposed to GluN1/2A/2Bcontaining pyramidal cells, interneurons are more enriched for GluN1/2B/2D-containing receptors, and the efficacy of ifenprodil at GluN1/2B/2D receptors is much less than at GluN1/2B receptors (Yi et al, 2019). A recent study in mouse cortex has revealed that parvalbuminergic interneurons mature via tonically active GluN2C/2D-containing receptors which transform the depolarizing signaling of ambient glutamate into an increase of dendritic complexity.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted, however, that, similar to their synaptic counterparts, NMDARex may also display a voltage-dependent Mg 2+ block. Although the extent of this block may be dependent upon the receptor subunit composition (27)(28)(29), it is also possible that some additional mechanism by which DMV neuronal excitability is modulated may also be involved. Given the observed plasticity occurs in glutamatergic synapses, the most metabolically economical means for removal of the Mg 2+ -dependent block of NMDARex and NMDARs may involve the activation of postsynaptic metabotropic glutamate receptors (56,57) which are distributed throughout the vagal brainstem (58)(59)(60)(61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…Since antagonists of NMDARex have been shown previously to have variable selectivity for NMDARs (27)(28)(29), and memantine in particular may antagonize α7 containing nicotinic receptors (30) as well as 5-HT3 receptors ( 31) which may modulate central vagal neurocircuits (32)(33)(34)(35)(36)(37)(38)(39), a series of experiments were conducted in which the effects of the NMDARex antagonist, memantine (30µM), as well as the NR2B subunit-containing NMDA receptor (primarily extrasynaptic) antagonist, ifenprodil (3M) (40) were assessed on evoked (synaptic) NMDAR-mediated currents.…”
Section: Selectivity Of Nmdarex Antagonists In Dmv Neuronsmentioning
confidence: 99%